Safety and efficacy of splenectomy in over 65‐yrs‐old patients with immune thrombocytopenia. (7th July 2013) - Gonzalez‐Porras, Jose R.; Escalante, Fernando; Pardal, Emilia; Sierra, Magdalena; Garcia‐Frade, Luis J.; Redondo, Santiago; Arefi, Maryam; Aguilar, Carlos; Ortega, Fernando; de, Erik; Fisac, Rosa M.; Sanz, Oscar; et al.
Abstract Aim Few studies specifically focus on elderly splenectomized immune thrombocytopenia (ITP) patients. Older patients with ITP and excellent health are often excluded from surgery splenectomy. We aimed to compare the safety and efficacy of splenectomy in elderly and non‐elderly ITP patients and to examine the effect of age on therapeutic response. Material and methods We carried out a retrospective analysis of a series of 218 patients who had undergone splenectomy for ITP. We compared the data from the elderly group (≥65 yrs, 57 patients) with the young group (<65 yrs, 162 patients). Results Surgical technique (laparoscopy or open laparotomy splenectomy) was comparable between the two age groups. The adjusted risk of major bleeding following splenectomy for elderly patients was three times that for young patients (OR 3.05, 95% CI: 1.44–6.52). The median duration of postoperative hospital stay was longer for elderly than for young patients (8 d vs. 4 d, P < 0.001). However, we identified a subgroup of elderly ITP patients, those aged between 65 and 70 yrs who had undergone laparoscopic splenectomy, with a low risk of postoperative complications. Of the 218 patients, 89% achieved a favorable response to splenectomy. A favorable response was significantly less common in elderly than in young people (79% vs. 92%, P = 0.005). However, we observed an acceptable long‐term control of ITP in the elderly group, in which the probability of maintaining response for 14 yrs after splenectomy was 56%. Conclusions Patients aged ≥65 yrs experienced negative effects on safety and efficacy outcomes of splenectomy for ITP, but further studies are needed to identify predictors of postsplenectomy outcomes in this group.